An international housing market in the British Isles: Evidence from business and medium-term cycles using a Friedman test. (February 2020) - Gray, David
It has been averred that there is an international market in housing (inter alia, Adams Z and Füss R (2010) Macroeconomic determinants of international housing markets. Journal of Housing Economics 19(1): 38–50; Helbling T and Terrones M (2003) When Bubbles Burst – Chapter II, World Economic Outlook . April. Washington, DC: IMF; Pomogajko K and Voigtländer M (2012) Co-movement of house price cycles – A factor analysis. International Journal of Housing Markets & Analysis 5(4): 414–427). Although some authors examine the business cycle range, the mechanism by which this comes about is more likely to reflect financial market integration and evidence for this should be found in the medium-term cycle range. As a case study, there is an analysis of three associated 'regional' housing markets and their price movements. Northern Ireland's economy is distinct but should be linked to the rest of the UK by common policy shocks, and to Eire through a mutual border. Using a Friedman test, it is found that even this small cluster is not integrated. It is asserted that a housing cycle has both a financial and a business component. As Drehmann et al. (Drehmann M, Borio C and Tstasaronis K (2012) Characterising the financial cycle: Don't lose sight of the medium term! BIS Working Papers, No. 380, Bank for International Settlements, June) argue, cycles in the medium-term range are significant in housing. A dual component approach highlights the relevance of cyclical interaction for both revealing integration and the need to intervene to moderate cyclical reinforcement for crisis-avoidance. After 1995, Dublin and London are found to be more integrated than before, which is consistent with the international city integration thesis of Holly et al. (Holly S, Pesaran H and Yamagata T (2011) The spatio-temporal diffusion of house prices in the UK. Journal of Urban Economics 69(1): 2–23). Lastly, a simple test for cyclical asymmetry indicates that there is highness (the obverse of deepness, where the troughs are deeper than peaks) in the UK financial cycle.